A comparative study of Mentha arvensis L. and Mentha haplocalyx Briq. by HPLC. Issue 2 (17th January 2018) - Zhao, Bing Tian; Kim, Tae In; Kim, Young Ho; Kang, Jong Seong; Min, Byung Sun; Son, Jong Keun; Woo, Mi Hee
Abstract: We have developed a new method to simultaneously determine five marker compounds in Menthae Herba via HPLC/PDA – including hesperidin (1 ), rosmarinic acid (2 ), diosmin (3 ), didymin (4 ) and buddleoside (5 ). The newly developed method was successfully used to analyse for two species ( Mentha arvensis L. and Mentha haplocalyx Briq.) of Menthae Herba, and the satisfactory results were obtained from the validation of developed method. The pattern analysis could greatly discriminate between M. arvensis L. and M. haplocalyx Briq. In conclusion, the proposed HPLC/PDA method is suitable for quality evaluation of Menthae Herba. Abstract :